The 2014 Annexation of Crimea – An Example of Disintegration of the State’s Territories - Rusnak, Oleksandr (Cluj-Napoca: Presa Universitară Clujeană, 2020)
One of the complex burning issues that arose in modem international relations is the annexation of Crimea in 2014, which became the consequence of priority task of the Russian Federation — to establish its control over the peninsula. This fact is confirmed not only by analytical materials or the evidence of the use of the Russian Black Sea Fleet from the Crimean bases in some military operations, but also by several attempts to capture it during the 1990s and 2000s. Russia got another chance to achieve its goal with the coming to power in Ukraine of pro-Russian President V. Yanukovych. After all, it was at the apogee of the Revolution of Dignity that the event under study took place. As it already has serious consequences for the peninsula and Ukraine as a whole, and may significantly affect the states of the entire Black Sea region, in our opinion, it is extremely important in this article to analyze in details not only the reasons and way of the annexation of Crimea, but also to try to assess this event as far as possible now. The use of a certain layer of specialized scientific literature, as well as numerous testimonies of participants in the studied processes allow to characterise more deeply and more clearly to show the prehistory and the course of the Russian invasion of the peninsula in 2014, to determine the key consequences of disintegration that took place.
Keywords: annexation, Crimean peninsula, Black Sea Fleet, Ukrainian-Russian relations